Onkologische Rehabilitation bei Mammakarzinom - Hass, Holger G. (Die Rehabilitation, 2024)
Die Prognose des Mammakarzinoms hat sich durch eine zunehmend individualisierte Therapie deutlich verbessert. Allerdings kann es infolge der multimodalen Behandlung und dem Einsatz neuer Medikamente zu einer Vielzahl von somatischen und psychischen Folgestörungen kommen. Nachfolgend werden typische sowie neue Therapie-induzierte Nebenwirkungen erörtert und die zur Rehabilitation notwendigen Maßnahmen vorgestellt.As a result of increasingly individualized and multimodal therapy, prognosis of breast cancer has improved significantly over the last years. However, multimodal treatment and the use of new medications can lead to a variety of somatic, sometimes new, side effects such as fatigue, polyneuropathy or autoimmune toxicities. This and the oncological diagnosis lead to a high level of psychological distress in the women affected and often to subsequent psychological disorders (sleep/anxiety disorders, depression, ...). Both the diverse complaints after oncological therapy and the increasingly improved overall prognosis underline the importance of multimodal rehabilitation concepts to improve quality of life and successful professional reintegration.In the following, these secondary disorders after breast cancer, their multimodal therapy and their significance for social-medical performance assessment are presented in more detail.
Keywords: Onkologische Rehabilitation; Brustkrebs; Krebs-assoziierte Fatigue; Chemotherapie-induzierte Polyneuropathie (CIPN)